IDENTIFICATION OF POROCEPHALUS STILESSI (PENTASTOMID) IN THE PERUVIAN SNAKE LACHESIS MUTA - Gárate C., Inés (2007)
A necropsy was conducted in a venomus snake Lachesis muta (Family Vipiridae), originary from Satipo, Junín. This snake was 1.95 cm long, 9 years old, and was captive at the serpentarium of Universidad Nacional Mayor de San Marcos, Lima. Four pentastomids were found in the corporal cavity and lung serosa. The parasites were fixed in 10% formol and cleared with lactofenol. The morphologic evaluation revealed that three of them were females (gonopore close to the end body and cylindrical body shape similar to an annelid) and one male (expanded front body and genital pore near the mouth). The parasites had 4 hooks where two of them showed some sclerotic appendixes compatible with adult forms. Females had 47 rings and a length of 8.3, 7.5 and 6.9 cm, respectively, while the male had 39 rings and a length of 3.7 cm. These characteristics corresponded to the species Porocephalus stilessi. This is the first report of this parasite in Peruvian snakes.